A Study on Factors Affecting Online Shopping Behavior: A Case Study of Karnal - Kapil Sharma, Yogesh Kumar, Rajiv Khosla (Forest Chemicals Review, 2022)
Firms and Consumers are showing a significant and quick development in business through the Internet. Several firms utilized the Internet having the objective of decreasing marketing expenses along with lowering the prices of their services as well as products for maintaining a competitive advantage in highly competitive marketplaces. An interesting trend that is attracting the attention of both researchers and practitioners is the increase in interest rate in the Internet as purchasing as well as shopping medium. The main goal is to determine the factors that impact consumers in the Karnal district’s online shopping buying behavior, as well as to determine whether various categories of online Karnal buyers, such as regular buyers, frequent buyers, occasional buyers, along with trial buyers; perceive website factors in various ways. The outcomes of the study revealed that every website feature has a vital impact on the attitudes of all online purchasers regarding online shopping. The findings indicate that vast majority of respondents under the age of 29 utilize the internet just for online shopping. Approximately 75% of those who answered the survey are recent graduates who buy on the internet.